Metodologías en contexto: intervenciones en perspectiva feminista/poscolonial/latinoamericana - Oto, Alejandro de (CLACSO, 2017)
The writings present here can be grouped from various entries, which are nothing more than a relatively arbitrary ordering but indicate, in a general way, the range of problems that we address. On the one hand, we work with research issues and problems linked especially to the theoretical-political critique of colonialism. On the other, there is a discussion hand in hand with contemporary feminisms. At another time, and in connection, from critical perspectives and within the framework of Latin American Thought, there are questions related to how, what, who and from where we ask questions, in what contexts and spatialities, how we relate to certain materials and how we intervene in them. , what domains we generate with their manipulation, how we work with them in relation to what we call, from cultural criticism, practical-theoretical.